The role of biomarkers in the early diagnostics of breast cancer - A. Kh. Ismagilov; D. R. Khuzina; A. S. Vanesyan; V. V. Zaysteva (Опухоли женской репродуктивной системы)
One of the main priorities in modern oncology is the identification and clinical application of biomarkers that can be helpful in the diagnostics and prognostication of cancer. The aim of this article was to review biomarkers for early diagnosis and prediction of prognosis of breast cancer. There were reviewed three main groups of biomarkers in this article: familial breast cancer biomarkers with high and low penetration (BRCA1, BRCA2, TP53, etc.), biomarkers of breast cancer molecular subtypes (luminal A and luminal B, HER2/neu, basal and low in claudine) and biomarkers of early stage breast cancer progression (multigenic panels).